Students’ Needs Analysis for Practical Anti-Plagiarism Guidelines in Polytechnic Higher Education - Fajar Aminullah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Academic integrity has become a very important issue in higher education recently, along with the high use of Generative AI technology in academic writing. This study aims to analyze students' needs for plagiarism prevention through practical anti-plagiarism guidelines in the Vocational Higher Education environment. This study applied a descriptive survey research design involving 80 students from four study programs in the Business Administration Department of the Pontianak State Polytechnic. Data were obtained through a structured questionnaire that assessed awareness of plagiarism, academic writing practices, digital literacy, use of reference managers, and the need for institutional support. The results of this study indicate that students already have a fairly good conceptual understanding of plagiarism, but still face difficulties in practice due to a lack of information or facilities for learning academic writing skills. This study found a gap between these two aspects, indicating a strong need for practical and easily accessible anti-plagiarism guidelines.